2D-HELS-AA MS Seq: Direct sequencing of tRNA reveals its different isoforms and multiple dynamic base modifications - Zhang, Ning; Shi, Shundi; Wang, Xuanting; Ni, Wenhao; Yuan, Xiaohong; Duan, Jiachen; Jia, Tony Z; Yoo, Barney; Ziegler, Ashley; Russo, James J; Li, Wenjia; Zhang, Shenglong (bioRxiv, 2019)
We report a direct method for sequencing tRNAPhe without cDNA by combining 2-dimensional hydrophobic RNA end-labeling with an anchor-based algorithm in mass spectrometry-based sequencing (2D-HELS-AA MS Seq). The entire tRNAPhe was sequenced and the identity, location and abundance of all 11 base modifications were determined. Changes in ratios of wybutosine and its depurinated form under different conditions were quantified, pointing to the ability of our technology to determine dynamic changes of nucleotide modifications. Two truncated isoforms at 3′ CCA tail of the tRNAPhe (75 nt CC, 80% and 74 nt C, 3%) were identified in addition to the 76 nt tRNAPhe with a full-length 3′ CCA tail (17%). We also discovered a new isoform with A-G transitions at both the 44 and 45 positions in the tRNAPhe variable loop.